Perception of risk and religiosity in the consumption of marijuana in adolescents from marginal areas - Fierro Herrera, Claudia Yanet; Candia Arredondo, Josefina Sarahi; Pillon, Sandra Cristina; Alonso Castillo, María Magdalena; Guzmán Facundo, Francisco Rafael (Horizonte Sanitario, 2023)
Objective: To describe the effect of the perception of risk and religiosity on the consumption of marijuana in adolescents from marginal areas of the State of Chihuahua, Chihuahua.Materials and methods: Study descriptive correlational design. The sampling was simple random probabilistic. The final sample consisted of 248 adolescents between the ages of 12 and 17 from marginal areas of Chihuahua. A personal data card, religiosity inventory and the risk perception scale were used.Results: 59.3% of the adolescents interviewed were men, of whom 59.7% said they were Catholic and 23% Christian. 16.1% indicated marijuana use at some time in their life, and 6.5% in the last year. The logistic regression model of the religiosity and risk perception variables showed an explained variance of 19% for marijuana use at some time in life, highlighting that the higher the risk perception (β=-0.032, p